INNOVATIVE WORK BEHAVIOR IN HIGHER EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Ardianti, Tanti; Tukiran, Martinus; Mariana, Diah (Research and Development Journal of Education, 2024)
Many studies have aimed to identify the factors influencing Innovative Work Behavior (IWB). However, there is still a lack of comprehensive research on these factors, particularly in the context of higher education. This research aims to identify the key factors affecting IWB within the higher education environment. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method, three relevant studies were selected and analyzed. This paper uses a literature review methodology, drawing from various sources. The findings suggest that five critical factors influence IWB in higher education: Innovation Culture, Collaborative Work Environment, Leadership Support, Resources and Facilities, and Student Engagement. These findings can help higher education institutions, academic researchers, and policymakers understand and promote innovative work behavior among faculty members. This study also contributes to bridging the research gap regarding IWB in higher education and offers insights for future research and interventions to enhance innovation among faculty members.